2005
DOI: 10.1385/scr:1:1:065
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and Tissue Regenerative Potential of Bone Marrow-Derived Cells

Abstract: Diverse in vivo studies have suggested that adult stem cells might have the ability to differentiate into cell types other than those of the tissues in which they reside or derive during embryonic development. This idea of stem cell "plasticity" has led investigators to hypothesize that, similar to embryonic stem cells, adult stem cells might have unlimited tissue regenerative potential in vivo, and therefore, broad and novel therapeutic applications. Since the beginning of these observations, our group has cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 45 publications
1
32
0
5
Order By: Relevance
“…These data are compiled from three independent experiments using MSCs derived from different donor samples. is a large body of confl icting results regarding the broader developmental potential of BM and blood stem cells and it remains a controversial issue in the stem cell research fi eld [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are compiled from three independent experiments using MSCs derived from different donor samples. is a large body of confl icting results regarding the broader developmental potential of BM and blood stem cells and it remains a controversial issue in the stem cell research fi eld [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…We are taking a simplifi ed approach to investigate if BM stem cells can differentiate into neural cells by using a subpopulation of stem cells instead of whole BM or blood cells. It has been reported that all identifi ed stem cell populations in the BM, including hematopoietic stem cells [44][45][46][47], MSCs [21][22][23][24][25][26][27][28], mesodermal adult progenitor cells [50], and others [51][52][53], possess the potential to differentiate into neural cells. However, MSCs are the most well-characterized stem cell population for the generation of neural cells, both in vitro and in vivo, and are the choice of stem cell population in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Hämatopoetische Vorläuferzellen können bei Zeitverzug bis zur Applikation bei Raumtemperatur gelagert werden, ohne Schaden zu nehmen [24]. Dennoch ist bei offensichtlich hoher Bioverträglichkeit eine Differenzierung in Kardiomyozyten rar [25] und eine Zellfusion mit Kardiomyozyten weitaus wahrscheinlicher [26]. Die Mechanismen, die heute mit den kardioprotektiven Effekten der Zellen in Verbindung gebracht werden, korrelieren weitgehend mit der Steigerung der myokardialen Perfusion und der Reduktion der Apoptoserate im Myokard [27,28].…”
Section: Mesenchymale Stammzellen Aus Dem Knochenmarkunclassified
“…Dabei ist der Mechanismus, der dazu führt, dass klinisch nach Injektion von mononukleären Zellen nicht über eine Zunahme von Arrhythmien berichtet wird, noch unklar. Zusammen mit der eher geringen Bereitschaft, zu Kardiomyozyten zu differenzieren [25], ist dies möglicherweise die Folge davon, dass die Zellen nicht über Gap Junctions, sondern durch ihre parakrine Aktivität im Zielgewebe mit den Herzzellen kommunizieren.…”
Section: Abb 2 8 Darstellung Der Gewebeveränderungen Nach Intramyokaunclassified
“…About a decade ago, many reports highlighted the broad developmental potential of bone-marrow-derived stem cells [1] . This gave new hope for cell therapy using autologous bone marrow cells, which has few ethical problems and has been applied to severe liver diseases [2] .…”
Section: Introductionmentioning
confidence: 99%